Preliminary Studies on the Rooting Response of Schefflera arboricola through Juvenile Shoot Cuttings - Nautiyal, S.; Prakash, Rakesh; Kumar, Niteesh (Indian Forester, 2015)
The rooting of juvenile shoot cuttings of Schefflera arboricola was studied during summer months 2013. Only one rooting hormone that is IBA in two concentrations i.e.2000 and 4000 ppm were applied to see the effect of rooting hormone. Maximum 65% rooting was observed in IBA 4000 ppm followed by 40% in IBA 2000 ppm and minimum 20% rooting recorded in control (Untreated cuttings).